Quantitative determination of glycyrrhizinic acid by square-wave - Aneta Dimitrovska; Svetlana Kulevanova; Valentin Mircevski (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2003)
Novel adsorptive stripping square-wave voltammetric method as well as a new high-pressure liquid chromatographic method for direct determination of glycyrrhizinic acid in dosage pharmaceutical preparation, used against virus infections, have been developed. Glycyrrhizinic acid is an electrochemically active compound, which undergoes irreversible reduction on a mercury electrode surface in an aqueous medium. Its redox properties were studied thoroughly by means of square-wave voltammetry, as one of the most advanced electroanalytical technique. The voltammetric response depends mainly on the pH of the medium, composition of the supporting electrolyte, as well as the parameters of the excitement signal. It was also observed that the voltammetric properties strongly depend on the accumulation time and potential, revealing significant adsorption of glycyrrhizinic acid onto the mercury electrode surface. Upon this feature, an adsorptive stripping voltammetric method for quantitative determination of glycyrrhizinic acid was developed. A simple, sensitive and precise reversed phase HPLC method with photodiode array UV detection has also been developed, mainly for comparison and conformation of the results obtained with the voltammetric method.